Aktualisasi Pemahaman Al-Qur'an Oleh Santri dengan Menggunakan Metode Wafa - Fadhila, Liqfa Nurul; Adisel, Adisel; Nurlaili, Nurlaili (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of the study was to determine the understanding of the Qur'an by using the Wafa method by students and to find out the application of the wafa method in understanding the contents of the Qur'an in the students of SMA Muhammadiyah 1 Boarding School. The research method used is a qualitative method. The research results are; 1) Students' understanding of the meaning and content of the Qur'an through the wafa method is not yet maximized. However, in general, the santri are at least able to understand the meaning and content of the Qur'an contained in juz 30 and the verses they are familiar with. Because learning the Qur'an using the wafa method is still relatively new, both schools, educators and students should learn more about what this wafa method actually is; 2) For the application of students' understanding of the contents of the Qur'an, it is still not maximally applied. Judging from the learning alone, it still emphasizes learning tahsin or justification of reading and emphasizes the hijaz song which is the song in the application of this wafa method. In conclusion, students' understanding of the meaning, content of the content of the Qur'an and the application of students' understanding of the contents of the Qur'an with the Wafa method is still not optimal, this is because the application of the Wafa method is relatively new at SMA Muhammadiyah 1 Boarding School. Keywords: Wafa Method, Application, Understanding the Qur'an